La obra musical del compositor lojano Benjamín Pinza Suárez y su aporte al desarrollo cultural de la identidad lojana. - Pogo Pineda, Jorge Vinicio P (2022)
In the imaginary of Loja people, it is considered the musical city of Ecuador, since it is inhabited by composers who have illustrated the city with their talent from past times to the present, among them we have: Segundo Cueva Celi, Salvador Bustamante Celi, Galo Terán Arteaga, Tulio Germán Bustos Cordero, Manuel de J. Lozano among others. Among the diversity of musicians, we find Dr. Benjamín Pinza Suárez, who with his vast work has given the city-wide recognition at a local, national and international level, highlighting in his productions the culture and identity of Loja. Pinza Suárez has a wide repertoire of genres such as: corridors, waltzes, boleros, albazos, ballads, zambas, among others, distributed in four musical discographies. In the present investigative work, it was proposed to index his musical work, which is in the Pinza Tapia family archive, that is, in their custody. For the scope of this project, the general objective was to contribute to the cultural development of Loja identity through the study of the work of Loja composer Benjamín Pinza Suárez. An interview was applied to the composer understudy for data collection, in which it was possible to theoretically analyze the reality of the composer's musical work, its location, which is not indexed so far, but it is necessary to elaborate the index of the musical work of the master, as a contribution to the cultural and artistic development of the city of Loja and the country. For the information processing, the following methods were used: biographical-narrative, scientific, descriptive, hermeneutical, expository and for the development of the alternative proposal, which consisted of chronologically indexing the musical work of Benjamín Pinza Suárez, to the analytical-synthetic method. The musical work of the composer Benjamín Pinza Suárez is located at his home, it has not yet been indexed or compiled; however, this is in a process of arranging in folders both his musical and literary compositions, videos, speeches, writings, and biographical sketches. The chronological index of the musical work of Pinza Suárez will allow it to be recognized and disseminated to citizens who are unaware of the musical work of the composer from Loja. It is suggested to the cultural authorities of the city of Loja, to take as a reference the proposal of this work as a contribution to the development of Loja culture. Keywords: Musical index, culture, lojan music.